The politics of old age : Older people's interest organisations and collective action in Ireland - Martha, Doyle (Book collections on Project MUSE., 2014)
The politics of old age in the twenty-first century is contentious, encompassing ideological debates about how old age is conceptualised and the rights and welfare entitlements of individuals in later life. This book situates the discussion in the international context and outlines findings of an Irish case study which explores the evolution of older people's interest organisations in Ireland from their inception in the mid-1990s to the end of the first decade of the twenty-first century.